Utilization of Nuclear Electricity in the Paradigm of Progressive Legal Theory - Taufik, Muhammad (Jurnal Ius Constituendum, 2024)
The purpose of this research is to examine the risks of utilizing nuclear power in terms of emission, footprint, ecosystem, and waste, examine the utilization of nuclear power in supporting the green economy, and examine the format of new and renewable energy law reform in the utilization of nuclear power as new energy in the paradigm of progressive legal theory. The research is motivated by the negative perception of nuclear energy without detailing the potential and advantages of nuclear energy through the application of nuclear power plants. Then, highlighting doubts about the use of nuclear energy in the green economy development agenda, as well as highlighting legal challenges in the framework of nuclear energy regulatory reform in Indonesia contained in the Draft Law on New and Renewable Energy (RUU EBT), By using normative and comparative juridical approaches, this research finds positive impacts of nuclear energy on the environment and green economic development by taking France as a successful example. To overcome legal problems in RUU EBT, this study recommends the application of a progressive legal approach in the formation of a legal policy model, as has been applied by the People's Republic of China (PRC) and Norway.